Be happy always : simple practices for overcoming life's challenges and living each day with joy - Ooi, Xandria (Tantor Audio, 2019)
Lift yourself out of the daily struggles and heartbreaks life deals you. Wading through the trials we face on a day-to-day basis can be exhausting. When we're hit with painful experiences that bring us to our knees, finding joy may seem to be too big a task for us to handle. Xandria Ooi, dubbed the "Happiness Guru," meets listeners in those dark and trying places and equips them with the courage to navigate them. Renew the meaning of happiness. Popular phrases like "think positive" and "look for the silver lining" often fall flat on our ears because we've heard them so many times. When life gets challenging, suddenly it's not so simple. Ooi shows us that happiness is more than a feeling by delving into complex philosophies and turning them into relatable wisdom. Find peace and joy within yourself, others, and your life. Joining the ranks of Brene Brown and Gretchen Rubin, Ooi speaks honestly and empathetically to listeners searching for answers. Creator of a thirty-day happiness program and over 500 motivational videos online, Ooi has traveled far and wide to share her inspiring stories and moving wisdom. Armed with her advice, listeners will find practical ways to bring more happiness to every aspect of their lives